Hybrid transanal and laparoscopic hand-assisted TME for low rectal cancer: report of a case - Samalavičius, Narimantas Evaldas; Dulskas, Audrius; Aliukonis, Vygintas; Račkauskas, Rokas; Kilius, Alfredas (Lietuvos chirurgija, 2016)
Total mesorectal excision (TME) is a widely accepted golden rectal cancer surgery standard. In low rectal cancer, there are a lot of important concerns related to sphincter saving, positive resection margins and similar aspects. We present a case of 52 year old female, who underwent a successful hybrid transanal and laparoscopic hand-assisted TME for low rectal cancer. Trials to delineate proper indications for low rectal cancer of robotic TME, transanal TME (Ta TME) and hybrid transanal plus laparoscopic TME are needed.